From the farm to the front : a South Gloucestershire family's experiences during the First World War, showing the effects on everyone from the Home Front to the Battle of the Somme /: a South Gloucestershire family's experiences during the First World War, showing the effects on everyone from the Home Front to the Battle of the Somme. (2017) - Harris, Adrian
No abstract available